Classification of factors determining the necessity for searching of a partner within innovative activities - Lisovska, l.; Karyy, O. (Видавництво Львівської політехніки, 2020)
In the article the authors substantiated the connection between the indicators of innovation activity efficiency and indicators of innovation cooperation in the course of innovation processes. The importance of research into the problems of forming systems of interaction in Ukraine has been proved. The advantages for the formation of systems of interaction in innovation, the goals of the formation of systems of interaction in different temporal dimensions and the principles of cooperation have been identified. The analysis of factors for the establishment of interaction, their grouping by a number of features was conducted. The authors have formed a system of factors for establishing interaction based on the concept of the value of establishing interaction. The system of factors covers the following five groups: cost property, information and communication, quality and market. Being set forth forcibly, the group of cost and property factors form the cost of interaction, while the groups of information and communications technology, quality and market factors guide the cost of interaction between the participants of the interaction system within innovative processes. The authors of the study justified the need to identify a separate new group of factors as well as the types of relationships of the selected factors with the factors grouped according to the traditional features of classification. For formation of the administrative decision concerning participation in the system of interaction in innovative processes subjects shall substantiate system of factors on functional aspects of implementation of innovative activity, define importance of each of them for achievement of the purposes of innovative process, as well as estimate power of influence of each factor on the determined criteria. Once the benefits and threats from participation in the system of interaction have been identified, the subject of innovative activity shall justify the decision regarding the innovation form. While carrying out the research, general scientific methods as well as methods of theoretical / applied innovation were used. In order to undertake the research, the authors involved general scientific and special principles, techniques and methods of scientific knowledge applied within the field of innovation management, in particular: semantic analysis, comparative analysis and method of systematization; grouping terms, factor analysis and synthesis, abstractlogic method.
Keywords: innovation activity; interaction; innovative cooperation; interaction building factors; partners; O31;; O12;; D70;; D25; 658.001.76; 330.341.1